Co-benefits of preserving urban farmland as climate change adaptation strategy: An emergy approach - Ying-Chieh Lee; Ya-Fang Liu (Ecological Indicators, 2023)
The potential of urban green infrastructure (UGI) for adapting to climate change has been recognized, but the inclusion of urban farmland as a measure of nature-based solutions (NBS) and its co-benefits to alleviate flood risk has rarely been assessed. This case study of the Guandu Plain in Taipei City assesses the co-benefits of using urban farmland as an NBS measure to adapt to extreme climate events. Five alternative land use practices (increasing the ridge height of paddy rice fields, citizen farming, simple leisure farms, nursery gardens, and large nature parks) were proposed to assess their co-benefits when using existing farmland to alleviate flood risks; co-benefits were also identified through a workshop. Emergy synthesis was applied to estimate the inflows of energy and materials, performance, costs, and environmental sustainability of each alternative land use practice. Results indicated that all proposed alternative land use practices had higher co-benefits than traditional practices such as paddy rice fields. The use of earth banks to withhold excess runoff improved renewable energy flows and decreased environmental loading by reducing inflow energies from the economic system. Citizen farming had the highest return of co-benefits. Our findings suggest that the use of UGI to alleviate excess runoff and other benefits can co-exist with use for adaptation to extreme climate events. NBS are an important concept and should be integrated into land use planning to promote urban farmland as an effective UGI strategy to adapt to climate change.